(untitled) (Web of Teachers: Inderscience Research, 2026)
This article presents the results and analyzes experimental studies on optimizing a new yarn twisting device. Based on the theoretical and experimental studies, recommended parameters for adjusting the yarn twisting device for producing different ranges of twisted yarn are provided. Optimal values for key parameters that effectively influence yarn quality during yarn preparation for spinning are also explored. A theoretical analysis of the motion laws of individual yarns drawn from the package during winding allowed us to obtain a dependence on their tension in steady-state operation. Theoretical principles for equalizing the tension of individual yarns twisted into pairs during winding allow for effective tension control. Theoretical relationships for determining the tension between the tension device and the yarn guide during the winding of paired yarns with specific quality indicators were obtained. A method for comparing the lengths of yarn components during winding was improved to assess the effectiveness of preparing individual yarns for spinning. A relationship has been developed between the number of turns imparted to spun yarn and its fineness parameters.